2022
DOI: 10.1155/2022/1838682
|View full text |Cite
|
Sign up to set email alerts
|

Brain Connectivity and Network Analysis in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease with no effective treatment or cure. ALS is characterized by the death of lower motor neurons (LMNs) in the spinal cord and upper motor neurons (UMNs) in the brain and their networks. Since the lower motor neurons are under the control of UMN and the networks, cortical degeneration may play a vital role in the pathophysiology of ALS. These changes that are not apparent on routine imaging with CT scans or MRI brain can be identified using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Other studies that examine the cell-autonomous effect of FUS variants show that restricted expression of FUS in the brain and spinal cord of mice is sufficient to promote dendritic attrition of UMN and LMN, alterations of dendritic spines and NMJs as well as behavior impairments (Qiu et al, 2014;Ho et al, 2021). Consistent with a loss of corticospinal connectivity observed in ALS and FTD-MND patients (Whitwell et al, 2011;Renga, 2022), Prp-FUSR521C mice had loss of dendritic branching and mature spines in UMN and a corresponding reduction in the number and size of presynaptic terminals in spinal motor neurons (Qiu et al, 2014). Brain atrophy and age-dependent cognitive defects in Prp-FUSR514G transgenic mice were also found to cause decreased dendritic spine density and LTP in the hippocampus of these mice (Ho et al, 2021).…”
Section: Fus: Synaptic Dysfunction In Als/ftd Models Of Diseasementioning
confidence: 76%
“…Other studies that examine the cell-autonomous effect of FUS variants show that restricted expression of FUS in the brain and spinal cord of mice is sufficient to promote dendritic attrition of UMN and LMN, alterations of dendritic spines and NMJs as well as behavior impairments (Qiu et al, 2014;Ho et al, 2021). Consistent with a loss of corticospinal connectivity observed in ALS and FTD-MND patients (Whitwell et al, 2011;Renga, 2022), Prp-FUSR521C mice had loss of dendritic branching and mature spines in UMN and a corresponding reduction in the number and size of presynaptic terminals in spinal motor neurons (Qiu et al, 2014). Brain atrophy and age-dependent cognitive defects in Prp-FUSR514G transgenic mice were also found to cause decreased dendritic spine density and LTP in the hippocampus of these mice (Ho et al, 2021).…”
Section: Fus: Synaptic Dysfunction In Als/ftd Models Of Diseasementioning
confidence: 76%
“…We started from the substantial observations that ALS is characterized by alterations in the structural and functional brain connectivity, both at the global and at the nodal level [6, 7,42,43], in line with hypothesized spread-out involvement of the brain. In a large ALS cohort study, we have previously shown that functional brain networks are more integrated and vulnerable in patients, and this hyper-connectivity progresses with the clinical evolution of the disease [12].…”
Section: Discussionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis disease occurs due to the gradual defcit of motor neurons either in the brain or the spinal cord [1][2][3][4]. Te development of unknown genes or pathophysiological processes is considered the main cause of the disease [3,5,6]. ALS is a complex disorder since it afects the whole body and causes paralysis.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians rely on various syndromes to identify the disease in its early stages, such as behavioral defcits or cognitive dysfunctions [1,[7][8][9][10]. If the disease is diagnosed behind time, then it could afect the treatment plan negatively [2,5]. Te efcient ways to predict and diagnose ALS disease are to look for related biomarkers and perform robust clinical evaluations using biological data [1,11,12].…”
Section: Introductionmentioning
confidence: 99%